Hubungan Antara Fear of Missing Out (FoMO) Dan Perilaku Konsumtif Di Kalangan Mahasiswa UKSW - Elena Okamelinda; Maria Goretti Adiyanti (GUIDENA: Jurnal Ilmu Pendidikan, Psikologi, Bimbingan dan Konseling, 2026)
This study aims to analyze the relationship between Fear of Missing Out (FoMO) and consumptive behavior among students of UKSW. The background of this research is based on the increasing use of social media and online shopping platforms, which encourages student consumption behavior through social pressure and the desire to follow trends. This study employed a quantitative approach with a correlational design and a purposive sampling technique involving 125 UKSW students aged 18–25 years. Data were collected using a FoMO scale based on the theory of Przybylski et al. and a consumptive behavior scale based on the theory of Lina and Rosyid. Data analysis using Spearman correlation revealed a significant positive relationship between FoMO and consumptive behavior (r = 0.699; p < 0.05). Higher levels of FoMO were associated with higher levels of consumptive behavior among students. These findings indicate that FoMO plays an important psychological role in shaping student consumptive behavior in the digital era.